Pemanfaatan Fly Ash Batubara dalam Penurunan Kadar Besi dan Mangan Limbah Air Asam Tambang PT Bukit Asam - Sari, Rahmaida; Yerizam, Muhammad; Junaidi, Robert (Universitas Pahlawan Tuanku Tambusai, 2024)
PT Bukit Asam Tbk is one of the largest coal producers in Indonesia. Fly ash, the primary waste from the operations of PLTU Bukit Asam, is a fine particle residue from coal combustion that can cause environmental pollution if not properly managed. Based on Government Regulation No. 22 of 2021, fly ash is no longer categorized as hazardous waste (B3), leading to increased research on its utilization. This study aims to utilize fly ash from PLTU Bukit Asam as an adsorbent to reduce iron (Fe) and manganese (Mn) content from acid mine drainage at PT Bukit Asam Tbk, using NaOH as a basic activator and varying contact time and adsorbent mass. Characterization of the fly ash morphology using Scanning Electron Microscopy (SEM) showed that activated fly ash has a more porous structure compared to before activation, increasing the specific surface area and adsorption potential. The study results indicated that the adsorption efficiency of Fe increased with the increasing adsorbent dose, reaching the highest efficiency of 99.95% at a dose of 500 grams and a contact time of 50 minutes. The Langmuir and Freundlich isotherm models were used to describe the adsorption process. The high determination coefficient (R²) values, ranging from 0.9474 to 0.9916 for Fe and 0.99602 to 0.99862 for Mn, indicate the suitability of these models in the studied adsorption system.